ANALISIS PENGUKURAN PERFORMANSI JARINGAN 4G LTE PADA AREA LAHAN KERING KEPULAUAN (STUDI KASUS DI WILAYAH AMARASI, KEC. TTS, NTT) - Clarita E. Kebos; Beby H.A. Manafe; Kalvein Rantelobo (Universitas Nusa Cendana, 2022)
This works takes samples and case studies in the Amarasi area, Kec. TTS, Prov. NTT; because there is still little literature and research conducted in rural areas, especially in the dry land of Semi-arid areas. Therefore, this study analyzes the measurement of the performance of the 4G LTE network, both voice and data communication, carried out in two different conditions, namely outdoor and indoor based on four parameters, namely RSRP, RSRQ, SNR and Throughput. The percentage of the RSRQ category is very good 32%, and bad 1%. The percentage of SNR category is very good 19%, and bad 1%. The average for throughput is 15.81 Mbps download and 18.41 Mbps upload which is good for Kotabes, Tunbaun and Nonbes villages. The measurement results in indoor conditions, the percentage of the RSRP category is very good 4%, and bad 24%. The percentage of SNR category is very good 23%, and bad 1%. The average throughput is 8.79 Mbps download and 11.57 Mbps upload; namely in the villages of Teunbaun, Tunbaun and Aprein. The results of the analysis show that the 4G LTE network has good and promising performance.